A Cross-Sectional Study on Perceptions of Nigerian Secondary School Students towards Persistent Teacher Strikes: Analyzing Causes, Government Actions, and Teachers' Engagement - , Chinecherem Johnbosco Obiekwe; , James Onukwu; , Sochima Johnmark Obiekwe; , Ezenwa Robinson Modum; , Gabriel Chidera Edeh; , Francis Chibuike Anigwe; , Chisom Jennifer Chima (Archives of Current Research International, 2023)
Teacher strikes have been a persistent issue in Nigeria, causing significant disruptions to the education system and negatively impacting students' learning outcomes. This study aims to examine the perceptions of Nigerian students regarding the causes of teacher strikes, the government's response, and the teachers' interest in strike actions. A random sample of 25 schools in Bayelsa state, located in the south-south geopolitical zone of Nigeria, was selected for this cross-sectional study. A total of 200 senior secondary students were randomly recruited to complete a questionnaire. The findings reveal that the majority of students attribute the causes of teacher strikes to delayed salary payments and other factors. Additionally, students hold a highly negative perception of the government's actions in response to strikes, perceiving a lack of attention and responsiveness. Students believe that the government has become desensitized to the impact of these strikes. Furthermore, the study suggests that students view teachers as beneficiaries of the strike, utilizing the opportunity to engage in private businesses, travel, and pursue further studies. Based on the study's results, it is concluded that students perceive teachers as having personal gains from the strikes. The study offers recommendations to address the issue of incessant strikes and change students' perceptions. These recommendations aim to reduce the occurrence of strikes and foster a more positive perception of teachers and the government's response to strike actions. In conclusion, this research underscores the need for proactive measures to address the causes of strikes and improve government intervention, while also addressing students' perceptions and fostering a conducive learning environment.